Special software design for data acquisition and experi-mental database management of electromagnetic launch system. (April 2020) - Tian, H; Xia, Y; Huang, F; Jin, Y; Wan, G; Ni, Y J; Li, B M
Abstract: Electromagnetic launching system is composed of the Electromagnetic Railgun (EMRG) and the large-scale Pulse Power System (PPS). According to the different test requirements of PPS and EMRG, the special master-slave distributed data acquisition software for electromagnetic launching system is designed by using LabVIEW graphic language. The test host and the sub-machines are multi-channel transient data acquisition systems based on PXI bus. The host PXI is used to measure the comprehensive parameters of the EMRG in multi-physical field. All sub-PXIs are used to diagnose the discharge current signals of each Pulse Forming Unit (PFU). The database management software uses C# programming language to design a friendly human-computer interaction interface, and uses SQL Server software to establish and manage the database, which realizes the comprehensive management of experimental data, tasks and resources involved in the EMRG experiments. The experimental information and experimental data are classified and filed, and the experimental data can be queried, and the experimental results can be analyzed and compared. The data acquisition and experimental database management software has perfect functions, friendly user interface, convenient operation, good versatility, and can also be used in other experimental occasions.